Guidance of Self-protection efforts during the covid-19 pandemic, through community empowerment activities in Kasugengan Kidul Village, Depok Cirebon - Iin Indawati; Aan Kunaedi; Anis Selawati; Elva Angela (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The impact of the Covid-19 pandemic in Indonesia continues increasing significantly, even positive cases reached up to 235,173,857 people. The existence of Student Work Study (KKM) activities is expected to make a positive contribution during the Covid-19 pandemic that hit Indonesia. In connection with the condition of the spread of Covid-19 which is still increasing, KKM implementation activities in Kesugengan Kidul village, Depok Subdistrict, Cirebon Regency must certainly be creative in order to stay safe and the purpose of activities is achieved. Starting from student fielding and data collection of partnership problems by applying health protocols properly. The method of carrying out activities is carried out with various efforts, including by providing education through leaflets, brochures, sticking brochures on the walls of elementary schools, by limiting the implementation of learning activities, provide education and examples of vitamins both tablets and derived from fruit in the form of nutritious foods that the body needs during the Covid-19 pandemic, even educating through door to door method to local citizen. Expectation of understanding and insight of citizens in the place of KKM partnerships are increasing about the prevention of Covid-19. The results and benefits of KKM activities towards partnerships include increasing public awareness of the prevention of Covid-19, one of which understands the importance of using masks, especially 2-layer masks. The community is more cooperative towards the efforts and programs of village officials to prevent the increase in the spread of the Covid-19 virus, increased citizen insight in partnership on vitamins needed and useful to increase endurance to fight covid-19 and discipline to implement health protocols in an effort to prevent and suppress the spread of Covid-19 in the partnership area of Kesugengan Kidul Village, Depok Subdistrict, Cirebon Regency.